The Concept of Amal Jamai According to The Prophets Tradition : An Overview - Mohd Nizho bin Abdul Rahman; Alias Azhar (Khazanah: Jurnal Studi Islam dan Humaniora, 2015)
This paper focuses on Islamic management issues as one of excel- lent legacies left by the Prophet (S.A.W). This paper will review the accomplishment of Islamic approach to management which had been practiced by the Prophet SAW and his companions. Based on archival research method, this paper will analyze the concept of Amal Jamai(team work) based on Islamic management centered onthetraditionsof theProphet(SAW).Thediscussionshowed that team work is an imperative element in Islamic management and not merely confined to the practice of dawah (inviting to Is- lam) but also in term of daily activities. In fact, the practice had been taught and shown by the Prophet (SAW). Even though the West had introduced many contemporary management theories, there is a huge difference compared to the Islamic approach to management. The concept of management in Islam does not merely based on material gained but also spiritual attainment and heavily emphasizes on the equality of the spiritual and material